INTRODUCTION WEB APPLICATION ANIMALS NAMES FOR BASIC SCHOOL STUDENTS USING Macromedia Dreamweaver 8.0 - Deni Suherman (Jurnal Sistem Informasi, 2007)
Along with the times and the more advanced technology, almost all people in the world using the Internet where the Internet provides information in terms of the field through a container known as a website. PT. Diamond Ice Cream, which is a website that contains information about products, price lists and order goods report. Scientific writing aims to be able to attract the attention of consumers. Making Website PT. Diamond Ice Cream is made using an application program Macromedia Dreamweaver MX, and as the Internet Explorer browser